The conservation of saproxylic beetles in boreal forest - Johansson, Therese (2006)
Forest management has altered the age structure, tree species composition and dead wood availability of Swedish boreal forests. As a consequence, many saproxylic (wood living) insect species have decreased in abundance and many species are threatened. New conservation-oriented forestry uses management measures to favour saproxylic species in managed forests. In my thesis, I evaluated the importance of these measures for saproxylic beetles and possible improvements by using a large-scale field experiment at ten sites in northern Sweden. The substrate types used in the experiment included burned and shaded logs, logs inoculated with two species of wood-decaying fungi, untreated control logs, created snags and the tops of the snags. The experiment was performed in three stand types: clear-cuts, mature managed stands and old-growth stands. Additionally, I performed attraction experiments to examine the attraction of saproxylic beetles to sporocarps and mycelia-infected wood of wood-decaying fungi in landscapes with different proportions of old spruce forest. Saproxylic beetles were affected by both forest management and dead wood characteristics. Snags differed from lying untreated logs and tops and supported different assemblages of saproxylic beetles and significantly higher numbers of several bark beetle and predator species. Tops attracted different assemblages from both snags and untreated logs. Burned logs supported a lower abundance of saproxylic beetles, particularly fire-favoured species and cambium consumers (especially Dryocoetes autographus, Hylurgops palliatus, Hylurgops glabratus and Hylastes cunicularius) and different assemblages of fire-favoured beetles, cambium consumers and predators from the untreated logs, probably because burning makes the cambium less suitable as food for bark beetles. However, some species were attracted to the burned logs. Log exposure proved to be important, especially on clear-cuts where shaded logs supported different assemblages of saproxylic beetles, particularly ...